Analysis of Parenting Patterns on Student Motivatio - Rohmaniyah, Nur Alfiyatur; Khamdun, Khamdun; Widianto, Eko (Journal of Education Technology, 2020)
The low level of discipline among elementary school students has resulted in a sustainable impact on students. The problem in this study is the level of student discipline which is less influenced by the lack of attention to the position of parents towards children. This study aimed to find out more about the position of democratic parents in the formation of discipline in learning for grade III SD students. This study used a qualitative approach and descriptive type in presenting the research data. The method used in data collection was using the method of observation, interviews, and field notes. The results showed that the position of democratic parents has a very strategic role in the formation of learning discipline for third grade elementary school students. Through the democratic parenting style, parents are able to provide learning assistance and the formation of student character. Not only have that students also been accustomed by parents to have regular activities in the family environment, especially in the discipline of learning. Therefore, the position of democratic parents plays a very important role in the formation of student learning discipline. The suggestions that can be taken from this study for parents are expected to be able to provide good learning assistance to children so that children have a high level of discipline and interest in learning.